Association Between Metabolic Syndrome and Mild Parkinsonian Signs Progression in the Elderly - Peng, Zeyan; Zhou, Rui; Liu, Dong; Cui, Min; Yu, Ke; Yang, Hai; Li, Ling; Liu, Juan; Chen, Yang; Hong, Wenjuan; Huang, Jie; Wang, Congguo; et al. (Frontiers in Aging Neuroscience, 2021)
Background: This study investigated the impact of metabolic syndrome on the progression from mild parkinsonian signs (MPS) to Parkinson’s disease (PD). Methods: A total of 1563 participants with MPS completed 6 years of follow-up. The diagnosis of metabolic syndrome was made according to Adult Treatment Panel III of the National Cholesterol Education Program. The evaluations of MPS and PD were based on the motor portion of the Unified Parkinson's Disease Rating Scale. Cox proportional hazard models were used to identify the association between metabolic syndrome and PD conversion. Results: Of the 1563 participants, 482 (30.8%) with MPS developed PD at the end of the follow-up. Metabolic syndrome (HR: 1.69, 95% CI: 1.29-2.03) was associated with the risk of PD conversion. Metabolic syndrome was associated with the progression of bradykinesia (HR: 1.85, 95% CI: 1.43-2.34), rigidity (HR: 1.36, 95% CI: 1.19-1.57), tremor (HR: 1.98, 95% CI: 1.73-2.32), and gait/balance impairment (HR: 1.66, 95% CI: 1.25-2.11). The effect of metabolic syndrome on the progression of bradykinesia and tremor was nearly two fold. Participants treated for two or three to four components of metabolic syndrome, including high blood pressure, high fasting plasma glucose, hypertriglyceridemia, and low HDL-C, had a lower risk of PD conversion. Conclusion: Metabolic syndrome increased the risk of progression from MPS to PD. Participants treated for two or more components of metabolic syndrome had a lower risk of PD conversion.